1987
DOI: 10.1164/arrd.1987.135.4.912
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dynamic Airway Compression on Breathing Pattern and Respiratory Sensation in Severe Chronic Obstructive Pulmonary Disease1–3

Abstract: Patients with severe COPD are frequently flow-limited during expiration at rest. When expiratory flow is at its maximum, application of negative pressure at the mouth should accentuate dynamic compression downstream from the flow-limiting segment (FLS) without substantially affecting flow or pressure upstream. The purpose of this study was to determine the ventilatory response to such intervention and to determine its effect on respiratory sensation. Such responses should reflect the effect of airway receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(58 citation statements)
references
References 11 publications
3
53
0
2
Order By: Relevance
“…(2,(6)(7)(8)(9)(10) Dyspnea can also be induced by EFL per se, probably through reflexes originating from the dynamic compression of the intrathoracic airways. (27) The findings of the present study corroborate the concept that DH plays an important role as an etiological factor for exercise limitation in patients with moderate to severe COPD. Therefore, two thirds of the patients evaluated in the present study were unequivocally DH+ (Table 2), and the extent of that phenomenon correlated with exercise intolerance and the consequent dyspnea (Figure 1).…”
Section: Discussionsupporting
confidence: 88%
“…(2,(6)(7)(8)(9)(10) Dyspnea can also be induced by EFL per se, probably through reflexes originating from the dynamic compression of the intrathoracic airways. (27) The findings of the present study corroborate the concept that DH plays an important role as an etiological factor for exercise limitation in patients with moderate to severe COPD. Therefore, two thirds of the patients evaluated in the present study were unequivocally DH+ (Table 2), and the extent of that phenomenon correlated with exercise intolerance and the consequent dyspnea (Figure 1).…”
Section: Discussionsupporting
confidence: 88%
“…The finding of O'DONNELL et al [49] that application of -9.7 cmH 2 O?L -1 ?s -1 of expiratory assistance for 4 min during inspiration and expiration caused unpleasant respiratory sensation can be attributed to negative pressure application differences. NEP, usually set at -5 cmH 2 O level, is applied only during expiration at five-to 10-breath intervals.…”
Section: Nep Techniquementioning
confidence: 94%
“…Dynamic hyperinflation is associated not only with increased inspiratory work due to PEEPi [7] but also with impaired inspiratory muscle function [8]. This, together with flow-limiting dynamic compression during tidal breathing, may contribute to dyspnoea in flow-limited COPD patients [9,10]. Indeed, in a study by ELTAYARA et al [9], the severity of chronic dyspnoea was found to correlate much more closely with flow limitation than with usual spirometric indices.…”
mentioning
confidence: 99%